Bio-Ecology of Coconut Eriophyid Mite, Aceria guerreronis Keifer and Yield Loss Due to its Infestation on Popular Coconut Cultivars - Ambily Paul (Department of Agricultural entomology, College of Agriculture, 2001)
Studies were conducted to understand the biology, ecology, population dynamics and rr .te-host interactions of A. guerreronis and to assess the yield loss on popular cultivars of coconut as influenced by nut characters and weather parameters. An abstract of the work done and the results are given below. Biology of A. guerreronis was studied under both laboratory and field conditions. The study indicated that a total period of 9.8 days was required for completing one generation under laboratory condition. Population dynamics of A. guerreronis in young buttons of susceptible and tolerant palms of variety WeT and Komadan was studied from February 2000 to January 2001. Population of mites under each tepal was counted by using cello tape embedding method. The results revealed that the population was the highest in nuts sampled from fifth bunch followed by fourth and sixth bunches in both susceptible and tolerant palms. The present study indicated that age of developing nut was the most critical factor in the study of population dynamics. Monthly mean population of A. guerreronis was correlated with weather parameters viz., temperature, relative humidity and rainfall prevailed during the time of sampling, probable time of mite entry and the total duration of critical age of the bunch. The results indicated that the relative humidity prevailed at the probable time ofmite entry alone had a positive correlation with population in the susceptible type of Ko mad an. The length to circumference ratio of young nuts and its influence on mite injury was observed. The results showed that round nuts having a length to circumference ratio of